Evaluación técnica económica de la implementación de geomallas en el rediseño estructural de la Av. León Febres Cordero - Zambrano Veliz, Elvyn Stalin (2025)
The technical and economic study on the incorporation of geogrids in the redesign of Av. León Febres Cordero aims to assess the feasibility and effectiveness of this material in the road rehabilitation process. Geogrids reinforce the pavement structure and, due to their properties, improve the load bearing capacity of the soil, which helps reduce deformations and prevent the formation of cracks. The study took into account various technical factors, including the geogrid’s load-bearing capacity, weather conditions, and the traffic passing through the road, contrasting the performance of traditional structures with those that include geogrids as reinforcement. Thus, pavement analysis techniques and structural simulations were used to assess stability and resistance in each variable........